PENGGUNAANÃ‚Â INSTRUCTIONALÃ‚Â MATERIALSÃ‚Â Ã‚Â UNTUKÃ‚Â MENINGKATKANÃ‚Â PEMAHAMANÃ‚Â MAHASISWAÃ‚Â Ã‚Â TENTANGÃ‚Â SISTEMÃ‚Â BAHANÃ‚Â BAKARÃ‚Â ELECTRONICÃ‚Â FUELÃ‚Â INJECTIONÃ‚Â Ã‚Â - MaulanaÃ‚Â , SonikaÃ‚Â ; Widjanarko, DwiÃ‚Â ; WahyudiÃ‚Â , - (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
Penelitian ini bertujuan untuk menyusun Ã‚Â Instructional Ã‚Â Materials Ã‚Â dan meningkatkan pemahamanÃ‚Â mahasiswa Ã‚Â tentang penggunaannya pada Ã‚Â sistem Electronic Fuel Ã‚Â injection pada mata kuliah Perakitan otomotif Ã‚Â II.Ã‚Â Desain penelitian adalah quasi experiment dengan pre dan pos Ã‚Â tes. Populasi penelitian adalah mahasiswa TeknikÃ‚Â Mesin Unnes yang mengikuti mata kuliah Perakitan otomotif Ã‚Â II yaitu Ã‚Â sejumlah 42 orang yang Ã‚Â terbagi dalam duaÃ‚Â kelompok. Hasil penelitian menunjukkan adanya peningkatan pemahaman mahasiswa tentang sistem vahan bakarÃ‚Â EFI setelah menggunakan Instructional Materials. Hasil belajar rataÃ¢â‚¬Ârata pre tes Ã‚Â adalah 60,92 dan rataÃ¢â‚¬Ârata pos tesÃ‚Â adalah 77,83. Dengan demikian terjadi peningkatan hasil belajar belajar sebesar 27,77% jika dibandingkan denganÃ‚Â sebelum menggunakan Instructional Materials pada sistem bahan bakar EFI.Ã‚Â This Ã‚Â research Ã‚Â aims Ã‚Â to Ã‚Â create Ã‚Â Instructional materials Ã‚Â and Ã‚Â to Ã‚Â increase Ã‚Â students Ã‚Â understanding of Ã‚Â lessonÃ‚Â about Ã‚Â the Ã‚Â use Ã‚Â instructional Ã‚Â materials Ã‚Â and Ã‚Â the Ã‚Â fuel Ã‚Â system Ã‚Â Electronic Ã‚Â Fuel Ã‚Â Injection Ã‚Â (EFI) Ã‚Â in Ã‚Â the Ã‚Â AutomotiveÃ‚Â Assembly II lecture, Mechanical Engineering students of State University of Semarang in 2009/2010. Ã‚Â The researchÃ‚Â used a quasiÃ¢â‚¬Âexperimental design; it is preÃ‚ÂtestÃ‚ÂpostÃ‚Âtest design. The population of this research was students whoÃ‚Â took Ã‚Â the Ã‚Â Automotive Ã‚Â Assembly Ã‚Â II Ã‚Â lecture, Ã‚Â Mechanical Ã‚Â Engineering Ã‚Â Department, Ã‚Â Semarang Ã‚Â State Ã‚Â UniversityÃ‚Â consisting of 42 students in two different group. Because there was only one class for this lecture, all students fromÃ‚Â the class were chosen to be population. The result of analyzed data is that there is improvement in the fuel systemÃ‚Â Electronic Fuel Injection (EFI) understanding after the use of Ã‚Â the instructional materials for Automotive AssemblyÃ‚Â II lecture. The average value before using instructional materials (preÃ¢â‚¬Âtest) was 60.92 and the average value afterÃ‚Â using Ã‚Â instructional Ã‚Â materials Ã‚Â (postÃ¢â‚¬Âtest) Ã‚Â was Ã‚Â 77.83. Ã‚Â Therefore, it can be stated that the use of instructionalÃ‚Â materials EFI fuel system has been well and effective in accordance with studentsÃ¢â‚¬â„¢ achievements. The achievementsÃ‚Â mentioned Ã‚Â here Ã‚Â are Ã‚Â the Ã‚Â achievements Ã‚Â of Ã‚Â students who Ã‚Â joined Ã‚Â the Ã‚Â Assembly Automotive Ã‚Â II Ã‚Â lecture Ã‚Â in which Ã‚Â theÃ‚Â achievements Ã‚Â value Ã‚Â was Ã‚Â improved Ã‚Â from Ã‚Â 27.77%; Ã‚Â the Ã‚Â percentage Ã‚Â before Ã‚Â using Ã‚Â instructional Ã‚Â materials Ã‚Â EFI Ã‚Â fuelÃ‚Â system.Keywords: instructional materials, electronic fuel injection (EFI)